The effect of using Lorsbach Model on Generative Thinking Skills of Fourth Scientific– Class of Females students in Mathematics (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the current research is to identify: "The effect of using Lorsbach model on generative thinking skills of fourth scientific class of females students in mathematics." The experimental design was chosen for two groups (experimental and control), and the research sample consisted of (64) female students of the fourth scientific class at AL-Ta'akhi high School for females , affiliated to the Baghdad Education Directorate -  Rusafa / 2 , for the academic year (2020 -2021).         The research  was limited to chapters (second, third and fourth), the choice was made by simple random selecting method, when classes (3 and 4) chosen to be represented by (32) females  students  in the experimental group that studied  mathematics according to the (Lorsbach) model, classes  (1 and 2) to be represented by (32) females students in the control group that studied  mathematics according to the ordinary  method. The two groups of the research were rewarded with the following variables: (IQ test, test of previous knowledge in mathematics, previous achievement in mathematics, chronological age calculated in months).     The scientific material and behavioral goals were determined according to Bloom's six cognitive levels, where the number reached (135) goals. The teaching plans were prepared for the two research groups. The generative thinking skills test, consisting of (28) objective and article paragraphs.  The researchers used the Alpha-Cronbach equation and the Pearson correlation coefficients to find stability of the research tool, and the T-test for the two independent samples. The data were processed using the statistical bag (SPSS). The results of the research  indicated that there is a statistically significant difference at the level of (0.05) between the average scores of the experimental group and the control group in favor of the experimental group which was taught  mathematics according to the (Lorsbach) model in the generative thinking skills test.